Unmet Need of Family Planning Among Married Women of Reproductive Age in Rural Areas of Manikganj District (Anwer Khan Modern Medical College Journal, 2019)
Aims: Introduction: Bangladesh has impressive gains in indicators related to population and family planning. Therefore, the unmet need for family planning should be addressed with utmost importance.Materials and Methods: A descriptive type of cross sectional study was conducted at four villages of Saturia Upazilla of Manikganj district to find out unmet need of family planning among married women of reproductive age including the status of contraceptive use and obstacles toward using family planning methods. The duration of study was from November 2017 to March 2018. The sample size was 480 in number.Results: In the study, 87.5% respondents were Muslims. Regarding level of education 18.75% of the respondents was illiterate, 22.19% of the respondents completed their primary education and 31.35% passed the secondary school certificate Examination. Most of the respondents (92.92%) were housewives. Out of 480 families, 51% belongs to nuclear family. 23.13% of the respondents had income below 10,000 Tk. and about 27.50% had an income more than 20,000 Tk. Among 480 respondents, 42.06% had 2 living children and about 33.78% had a single child. 89.17% of the respondents knew about contraceptive method. OCP was the most preferred method among 57.62% respondents. 61% respondents were using contraceptive method. The reason for not using any contraceptive method were fear of side effects (28.03%), eager to conceive (13.63%), and non-co-operative attitude of the husband (7.58%). In this study 58.13% respondents had the knowledge about permanent method of contraception.Conclusion: Family planning is more of a health necessity than an option. Though family planning program has remarkable success over the past decade, but still there is unmet need.Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 23-27